Pedagogical monitoring of the moral culture of a preschool child - Olga A. Beznosova; Artur M. Allagulov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper is devoted to the problem of complex pedagogical monitoring of the development of moral culture of preschool children. The issues addressed in the paper are updated by the contradiction existing in psychological and pedagogical research between the extensive attention of science to the issues of moral education, the moral development of the personality and the uncertainty of the assessment criteria and the corresponding means of pedagogical monitoring of the development of moral culture among preschoolers. The options for monitoring the moral culture of children proposed by researchers do not reflect a general understanding of moral culture, focusing on its individual aspects (national values, Orthodox moral categories, various moral qualities, etc.), which is undoubtedly significant for science and practice. However, the tasks of preschool education, dictated by modern standards, require a qualitatively new approach to a holistic and comprehensive assessment of the results of the education of moral culture, which emphasizes the need to create, describe and empirically test a model of integrated pedagogical monitoring of the development of moral culture among preschoolers. Within the framework of the model of complex pedagogical monitoring of the development of moral culture among preschoolers described in the paper, a three-stage monitoring procedure is proposed. It allows to conduct a comprehensive assessment of the moral development of children according to cognitive, emotional-evaluative and behavioral criteria. Empirical testing has shown that the proposed monitoring procedure corresponds to the solution of the tasks set, makes it possible to assess both individual criteria and the general level of development of the moral culture of preschoolers, and the results obtained are correlated with expert assessments and observations of teachers and educators.